Perancangan Purwarupa Alat Penyiraman Otomatis pada Tanaman Pisang dengan Internet of Things (IoT) - Fadjri Ramadhan; Irfan Ardiansah; Roni Kastaman (Jurnal Rekayasa Sistem Industri, 2019)
Banana is one of the commodities that have nutritional value and high economic value. In order to produce a nice fruit and a high economic value, these plants must grow well. The Factors that can cause the plant to grow well, one of them is water. Water is used by plants, to grow root, stem, leaves and also maturation the fruit. When the plant doesn’t have water, growth will be stunted even death. In addition to deficiencies, excess water on the plant can also cause spoilage. Therefore, needed a tool which can watering plants, especially banana plant. The tool can be made using Arduino. Arduino is brand platform microcontroller that can control various sensors from soil moisture sensor, humidity sensor even it can apply the concept of the Internet of Things. The purpose of this research is to create a prototype automatic watering tool uses concept of the Internet of Things (IoT) to find out the condition of banana plant in real-time. The results obtained, the automatic watering tool successfully built and functional according the design, starting from the arduino that can control the soil moisture sensor to read current soil moisture, insert the data into the database, and the pump doesn’t on, because the moisture didn’t under 41% or in dry condition during the research. These data also sent to the user with a method of push notification.Keywords: Arduino, Banana, Internet of Things, Pushbullet, Push notification